THE INCREASING OF HYDROMINERAL PROCESSES' CONTROL EFFECTIVENESS WITH THE ACCOUNTING DISCOUNT OF MIGRATION COEFFICIENT'S NONUNIFORMITY - Alexander Vitalevich Martirosyan (Современная наука и инновации)
In this work the analysis of a migration coefficient's nonuniformity influence on the geofiltration processes modeling is given. The analysis of open-loop control system's frequency response was done. Nagutskoe mineral water field is provided as a control object.